A double-blind randomized controlled trial of topical Curcuma xanthorrhiza Roxb. on mild psoriasis: clinical manifestations, histopathological features, and K6 expressions (Faculty of Medicine Universitas Indonesia, 2018)
Background: Curcuma xanthorrhiza Roxb. exerts its anti-inflammatory effects by reducing the concentration of IL-6, IL-8, and phosphorylase kinase, which has role in keratinocyte proliferation. Our study aimed to evaluate the efficacy of C. xanthorrhiza in psoriasis.Methods: From 18 to 59 year-old patients with mild psoriasis, 2 similar lesions were selected. The severity assessment was based on the psoriasis area severity index (PASI), Trozak score, and K6 expression. Using a double-blinded randomized method, lesion was treated with 1% C. xanthorrhiza ointment vs placebo for 4 weeks. The results were analyzed by the chi-square test using STATATM V.12 software (Stata Corp.).Results: The study was conducted in 2010 to 2012 with 17 subjects participated. The median of PASI score were reduced significantly in both lesions, either treated with 1% C. xanthorrhiza ointment vs placebo; however when compared between the group, it was not significant (p=0.520). The Trozak score were reduced in lesions treated with 1% C. xanthorrhiza ointment; but it was not significant (p = 0.306). In lesions treated with placebo, the Trozak score was increased significantly. The difference of Trozak score between lesions treated with C. xanthorrhiza and placebo was significant (p=0.024). There was no significant difference of K6 expression in lesions treated with 1% C. xanthorrhiza ointments or placebo as well as on the difference of mean values of K6 expression between the group (p=0.827).Conclusion: Based on the results, 1% C. xanthorrhiza ointment is effective treatment option for mild psoriasis, but longer follow-up period is suggested to confirm this results. C. xanthorrhiza ointment is safe for topical administration as there were no side effects reported in this study.